KAMPUNG AKUARIUM COMMUNITY PARTICIPATION IN RESOLVING CONFLICT BETWEEN ARCHEOLOGICAL RESOURCE PRESERVATION AND APARTMENT BUILDING CONSTRUCTION - Hasnawati, Shella Dwiastu; Rahardjo, Supratikno (International Review of Humanities Studies, 2023)
Vertical housing is often considered a viable solution to address the high population density in DKI Jakarta. However, it poses a challenge when such housing is situated within Cultural Heritage zones that require preservation. This scenario gives rise to potential conflicts of interest between the preservation of archaeological resources and the development of housing for the public's benefit, as exemplified in Kampung Akuarium. This study aims to elucidate the extent of community involvement in resolving the issues arising from apartment development within cultural heritage zones. It emphasizes the need for balanced community participation to achieve a win-win solution. The research methodology employed in this explanatory qualitative study entailed conducting in-depth interviews and direct field observations. The data collected revealed the Kampung Akuarium community's participatory approach in addressing the conflict of interest. The local community actively participated in both the development of the apartment complex and the preservation of archaeological resources. Their involvement was evident during the planning stage, policy implementation, and the actual development of the apartment complex situated in the cultural heritage zone. This collaborative participation has fostered harmonious preservation of archaeological resources while meeting the housing needs of the Kampung Akuarium community.